Transvenous embolization of a Borden III middle cranial fossa dural arteriovenous fistula through the vein of Trolard and superficial middle cerebral vein: A technical case report - Yoshinori Kadono, MD, PhD; Kazushige Maeno, MD (Radiology Case Reports, 2024)
Endovascular treatment for isolated dural arteriovenous fistula (DAVF) in the middle cranial fossa (MCF) with pure cortical venous drainage poses challenges, including the absence of a safe access route for transvenous embolization (TVE) and the risk of ischemia to neuro feeding vessels and dangerous anastomosis at the sphenoid wing. Therefore, surgical treatment involving direct blockage of venous reflux via craniotomy is typically preferred. We describe the case of a 63-year-old woman presented with generalized seizures and was diagnosed with a Borden III left MCF-DAVF. Initial TVE was unsuccessful due to an occluded inferior petrosal sinus and a lack of connection between the cavernous sinus and the shunt point. After reducing the shunt flow with transarterial embolization, retrograde TVE through cortical drainage enabled successful treatment for the DAVF. We used a triple coaxial system (4-French guiding sheath, 3.2-French intermediate distal access catheter, and 1.5-French microcatheter) to retrogradely navigate a microcathter from the right jugular vein through the superior sagittal sinus, the vein of Trolard, and into the superficial middle cerebral vein, ultimately achieving shunt occlusion using several coils. This case demonstrates that TVE for MCF-DAVFs with pure cortical venous drainage is feasible when a safe anatomical route is established using appropriate strategies and instruments and provides a safe and effective treatment option for similar cases.